Interpersonal and Organizational Skills: Exercising Leadership in Language Teaching (Journal of Science-Innovative Research in Uzbekistan, 2024)
The current paper outlines a research plan developed to explore the implementation of a “Leadership Module” into the university level curriculum to improve English proficiency skills through leadership-related exercises. The module was created to endow students with academic and other transferable skills necessary to succeed in a higher educational setting. Namely, the module addresses academic listening, elementary critical reading, factual and opinion delineation writing, and information synthesis skill. The research is set to describe how leadership skills can be taught in a language teaching module to enhance other skills through them, namely, interpersonal interaction, personal organization, and program organization through theoretical framework and examples found in published sources. The research essentially grants the necessary leadership exposure to language education that is vital to the satisfaction of the teacher and learners, providing actionable findings to improve Implemented in university English courses